Laminate, electronic device, cover glass and resin composition

By setting a resin layer with specific properties on the thin glass plate, the problem of insufficient impact resistance of thin glass in the prior art is solved, and efficient impact protection is achieved, and suitable for foldable electronic devices.

JP7628658B2Active Publication Date: 2025-02-10SEKISUI CHEMICAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024542163
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-12-27
Publication Date
2025-02-10
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

In the prior art, the protective resin layer for thin glass has shortcomings in improving impact resistance, and the composition of the resin composition is not fully considered, resulting in thin glass being easily damaged in electronic devices.

Method used

A thin glass plate with a thickness of 200 μm or less is used, and a resin layer with a thickness of 5 μm or more is provided on one or both sides of the thereof. The storage modulus of the resin layer is 2500 MPa or less, the Young's modulus is between 50 MPa and 1500 MPa, and the glass transition temperature is 100°C or less. The resin layer consists of a hydrogenated bisphenol-type epoxy resin, an epoxy resin with a polyether framework and an oxetane group resin.

Benefits of technology

It significantly improves the impact resistance of thin glass, ensures the foldability and durability of electronic devices, and prevents fragments from flying away when the glass breaks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628658000003
    Figure 0007628658000003
  • Figure 0007628658000001
    Figure 0007628658000001
  • Figure 0007628658000002
    Figure 0007628658000002
Patent Text Reader

Abstract

One purpose of the present invention is to provide a laminate that has superior impact resistance. Another purpose of the present invention is to provide an electronic device and a cover glass that are obtained using said laminate, and a resin composition that is used in order to form a resin layer of said laminate. A laminate according to the present invention has a thin glass sheet that has a thickness of 200μm or less, and a resin layer that is positioned on at least one side of the thin glass sheet and has a thickness of 5μm or greater, wherein the fracture energy of the resin layer is 1 mJ / mm3 or greater, and the storage modulus at 25°C is 2500 MPa or less. Alternatively, a laminate according to the present invention has a thin glass sheet that has a thickness of 200μm or less, and a resin layer that is positioned on at least one side of the thin glass sheet and has a thickness of 5μm or greater, wherein the Young's modulus of the resin layer is 50 MPa to 1500 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate having excellent impact resistance. The present invention also relates to an electronic device and a cover glass using the laminate, and a resin composition used to form a resin layer of the laminate. [Background technology]

[0002] In recent years, development has been underway to make the display screens of electronic devices such as smartphones, e-books, and tablet PCs foldable. The use of flexible thin glass on the outermost surface side of such foldable display screens has been considered.

[0003] Since thin glass is easily broken by impact, it has been considered to dispose a protective resin layer on one side of the thin glass. For example, Patent Document 1 describes a protective substrate for a display device that includes glass and a resin layer on one side of the glass, in which the glass has a thickness of 20 μm to 200 μm and the specific gravity of the resin layer is 0.9 g / cm. 3 ~1.5g / cm 3 and the resin layer has a flexural modulus of elasticity of 1000 MPa to 8000 MPa at 25° C. Patent Document 2 also describes a protective substrate for a display device, which has a thin glass having a thickness of 120 μm or less and an impact absorbing layer having a thickness of 5 μm or more arranged on one side of the thin glass, and the impact absorbing layer has a flexural modulus of elasticity of 1000 MPa to 8000 MPa at 25° C. 1 ~10 15 An optical laminate having a maximum value of tan δ in the range of 1000 Hz is described. Patent Document 3 describes a cover member having a structure in which a glass plate having a thickness of 500 μm or less and a resin film are laminated via an adhesive layer. Patent Document 4 describes a display device substrate including inorganic glass and resin layers arranged on both sides of the inorganic glass. However, with regard to resin compositions for forming resin layers for protecting thin glass, sufficient consideration has not been given to the composition from the viewpoint of improving impact resistance, and resins with insufficient impact resistance have been used in the past, and therefore there has been a demand for further improvement in impact resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-37207 A [Patent Document 2] International Publication No. 2018 / 190208 [Patent Document 3] International Publication No. 2020 / 153259 [Patent Document 4] JP 2008-107510 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a laminate having excellent impact resistance. Also, the present invention aims to provide an electronic device and a cover glass using the laminate, and a resin composition used to form a resin layer of the laminate. [Means for solving the problem]

[0006] Disclosure 1 provides a glass substrate having a thickness of 200 μm or less and a resin layer having a thickness of 5 μm or more that is disposed on at least one side of the thin glass, the resin layer having a fracture energy of 1 mJ / mm 3 The laminate (first laminate) is as described above and has a storage modulus at 25° C. of 2500 MPa or less. The present disclosure 2 is the laminate of the present disclosure 1, wherein the Young's modulus of the resin layer is 50 MPa or more and 1500 MPa or less. The present disclosure 3 is the laminate according to the present disclosure 1 or 2, wherein the storage modulus of the resin layer at 25° C. is 2000 MPa or less. Disclosure 4 is the laminate according to Disclosure 1, 2, or 3, wherein the resin layer has a glass transition temperature of 100° C. or lower. The present disclosure 5 is the laminate of the present disclosure 1, 2, 3, or 4, wherein the resin layer contains a polymer of a cationically curable resin. The present disclosure 6 is the laminate according to the present disclosure 5, wherein the cationically curable resin contains an epoxy group-containing compound and an oxetanyl group-containing compound. The present disclosure 7 is the laminate according to the present disclosure 6, wherein the epoxy group-containing compound contains a hydrogenated bisphenol type epoxy resin. The present disclosure 8 is the laminate according to the present disclosure 7, wherein the hydrogenated bisphenol epoxy resin contains a hydrogenated bisphenol A skeleton. The present disclosure 9 is the laminate according to the present disclosure 7 or 8, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2000 or less. The present disclosure 10 is the laminate according to the present disclosure 6, 7, 8, or 9, wherein the epoxy group-containing compound includes an epoxy resin having a polyether skeleton. Disclosure 11 is the laminate of Disclosure 10, wherein the epoxy resin having a polyether skeleton is liquid at 23°C. The present disclosure 12 is the laminate according to the present disclosure 6, 7, 8, 9, 10, or 11, wherein the oxetanyl group-containing compound is monofunctional. The present disclosure 13 is the laminate according to the present disclosure 5, 6, 7, 8, 9, 10, 11, or 12, wherein the cationically curable resin contains a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, and an oxetanyl group-containing compound. The present disclosure 14 is the laminate of the present disclosure 13, wherein the content of the hydrogenated bisphenol type epoxy resin in the resin layer is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less. Disclosure 15 provides a glass substrate having a first resin layer having a thickness of 5 μm or more arranged on one side of the thin glass sheet, and a second resin layer having a thickness of 5 μm or more arranged on the opposite side of the thin glass sheet to the first resin layer side, wherein both the first resin layer and the second resin layer have a breaking energy of 1 mJ / mm 3 The laminate of Disclosure 1 is as described above, and has a storage modulus at 25° C. of 2500 MPa or less. A sixteenth aspect of the present disclosure is the laminate of the fifteenth aspect of the present disclosure, wherein the first resin layer and the second resin layer each have a Young's modulus of 50 MPa or more and 1500 MPa or less. Disclosure 17 is the laminate of Disclosure 15 or 16, wherein at least one of the first resin layer and the second resin layer has a thickness of 25 μm or less. Disclosure 18 is the laminate of Disclosure 15, 16, or 17, wherein at least one of the first resin layer and the second resin layer has a glass transition temperature of 100° C. or lower. Disclosure 19 is the laminate of Disclosure 15, 16, 17, or 18, wherein at least one of the first resin layer and the second resin layer contains a polymer of a cationically curable resin.

[0007] Disclosure 20 is a laminate (second laminate) having a thin glass sheet having a thickness of 200 μm or less and a resin layer having a thickness of 5 μm or more arranged on at least one side of the thin glass sheet, the resin layer having a Young's modulus of 50 MPa or more and 1500 MPa or less. The present disclosure 21 is a method for manufacturing a resin layer having a fracture energy of 1 mJ / mm 3 This completes the laminate of the 20th disclosure. Disclosure 22 is the laminate of Disclosure 20 or 21, wherein the resin layer has a storage modulus at 25° C. of 2500 MPa or less. Disclosure 23 is the laminate of Disclosure 20, 21, or 22, wherein the resin layer has a glass transition temperature of 100° C. or lower. Disclosure 24 is the laminate of Disclosure 20, 21, 22, or 23, wherein the resin layer comprises a polymer of a cationically curable resin. Disclosure 25 is the laminate of Disclosure 24, wherein the cationically curable resin includes an epoxy group-containing compound and an oxetanyl group-containing compound. Disclosure 26 is the laminate of Disclosure 25, wherein the epoxy group-containing compound includes a hydrogenated bisphenol type epoxy resin. Disclosure 27 is the laminate of Disclosure 26, wherein the hydrogenated bisphenol epoxy resin contains a hydrogenated bisphenol A skeleton. Disclosure 28 is the laminate of Disclosure 26 or 27, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2000 or less. Disclosure 29 is the laminate of Disclosure 25, 26, 27, or 28, wherein the epoxy group-containing compound includes an epoxy resin having a polyether skeleton. Disclosure 30 is a laminate according to Disclosure 29, in which the epoxy resin having a polyether skeleton is liquid at 23°C. The present disclosure 31 is the laminate of the present disclosure 25, 26, 27, 28, 29, or 30, wherein the oxetanyl group-containing compound is monofunctional. The present disclosure 32 is the laminate of the present disclosure 24, 25, 26, 27, 28, 29, 30, or 31, wherein the cationically curable resin includes a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, and an oxetanyl group-containing compound. The present disclosure 33 is a laminate of the present disclosure 32, in which the content of the hydrogenated bisphenol type epoxy resin in the resin layer is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less.

[0008] Disclosure 34 is a laminate of Disclosure 20, comprising a first resin layer having a thickness of 5 μm or more arranged on one side of the thin glass, and a second resin layer having a thickness of 5 μm or more arranged on the side of the thin glass opposite the first resin layer, wherein both the first resin layer and the second resin layer have a Young's modulus of 50 MPa or more and 1500 MPa or less. Disclosure 35 is the laminate of Disclosure 34, wherein at least one of the first resin layer and the second resin layer has a storage modulus at 25° C. of 3000 MPa or less. Disclosure 36 is the laminate of Disclosure 34 or 35, wherein at least one of the first resin layer and the second resin layer has a thickness of 25 μm or less. Disclosure 37 is the laminate of Disclosure 34, 35, or 36, wherein at least one of the first resin layer and the second resin layer has a glass transition temperature of 100° C. or lower. Disclosure 38 is the laminate of Disclosure 34, 35, 36, or 37, wherein at least one of the first resin layer and the second resin layer contains a polymer of a cationic curable resin. Disclosure 39 is the laminate of Disclosure 38, wherein the cationically curable resin includes an epoxy group-containing compound and an oxetanyl group-containing compound. Disclosure 40 is the laminate of Disclosure 39, wherein the epoxy group-containing compound includes a hydrogenated bisphenol type epoxy resin. Disclosure 41 is the laminate of Disclosure 40, wherein the hydrogenated bisphenol epoxy resin contains a hydrogenated bisphenol A skeleton. Disclosure 42 is the laminate of Disclosure 40 or 41, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2000 or less. Disclosure 43 is the laminate of Disclosure 39, 40, 41, or 42, wherein the epoxy group-containing compound includes an epoxy resin having a polyether skeleton. Disclosure 44 is the laminate of Disclosure 43, in which the epoxy resin having a polyether skeleton is liquid at 23°C. The present disclosure 45 is the laminate of the present disclosure 39, 40, 41, 42, 43, or 44, wherein the oxetanyl group-containing compound is monofunctional. The present disclosure 46 is the laminate of the present disclosure 38, 39, 40, 41, 42, 43, 44, or 45, wherein the cationically curable resin includes a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, and an oxetanyl group-containing compound. The present disclosure 47 is the laminate of the present disclosure 46, in which the content of the hydrogenated bisphenol type epoxy resin in the resin layer containing the polymer of the cationic curable resin is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less.

[0009] The present disclosure 48 is an electronic device including any one of the laminates of the present disclosures 1 to 47. Disclosure 49 is a cover glass comprising any one of the laminates of Disclosures 1 to 47. Disclosure 50 is a resin composition used to form a resin layer of any of the laminates of Disclosures 1-47. The present disclosure 51 is a resin composition containing a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, and an oxetanyl group-containing compound. Disclosure 52 is a resin composition according to Disclosure 50 or 51 used for application to thin glass having a thickness of 200 μm or less. Disclosure 53 is the resin composition of Disclosure 51 or 52, wherein the hydrogenated bisphenol type epoxy resin contains a hydrogenated bisphenol A skeleton. Disclosure 54 is the resin composition of Disclosure 51, 52, or 53, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2000 or less. Disclosure 55 is the resin composition of Disclosure 51, 52, 53, or 54, wherein the epoxy resin having a polyether skeleton is liquid at 23°C. The present disclosure 56 is the resin composition according to the present disclosure 51, 52, 53, 54, or 55, wherein the oxetanyl group-containing compound is monofunctional. The present disclosure 57 is a resin composition according to the present disclosure 51, 52, 53, 54, 55, or 56, in which the content of the hydrogenated bisphenol type epoxy resin is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less. The present invention will be described in detail below.

[0010] The present inventors have studied the resin layer disposed on at least one side of the thin glass sheet, and have focused on the correlation between the fracture energy and storage modulus of the resin layer and the impact resistance. 3 It has been found that sufficient impact resistance can be obtained by setting the storage modulus at 25° C. to 2500 MPa or less. Furthermore, the present inventors have studied the resin layer disposed on at least one side of the thin glass sheet, and as a result have focused on the correlation between the Young's modulus of the resin layer and impact resistance, and have found that sufficient impact resistance can be obtained by setting the Young's modulus to be 50 MPa or more and 1500 MPa or less. Furthermore, the present inventors have investigated improving the impact resistance of thin glass placed on the display surfaces of electronic devices by laminating a resin layer on its surface, and have found that glass shattering can be effectively prevented by providing resin layers on both sides of the thin glass, and that impact resistance can be improved by adjusting the breaking energy of the first and second resin layers to a combination of breaking energy and storage modulus or Young's modulus within a specific range. The present inventors have found a resin composition suitable for forming a resin layer in which the breaking energy, storage modulus at 25° C., and Young's modulus are adjusted to fall within specific ranges. In this manner, the present inventors have completed the present invention.

[0011] The laminate of the present invention (hereinafter, matters common to the first laminate and the second laminate are also referred to as "the laminate of the present invention") has a thin glass having a thickness of 200 μm or less and a resin layer having a thickness of 5 μm or more arranged on at least one side of the thin glass. At least one of the resin layers may be provided in the laminate of the present invention. For example, one or more resin layers may be arranged on one side of the thin glass, or one or more resin layers may be arranged on each of both sides. The laminate of the present invention may also have another layer other than the thin glass and the resin layer. For example, the resin layer may be laminated with the thin glass via an adhesive layer, but it is preferable that the resin layer is in direct contact with the thin glass without an adhesive layer. From the viewpoint of making the most of the advantages of using a flexible thin glass, a configuration in which only one resin layer is arranged on one side of the thin glass, or a configuration in which one resin layer is arranged on each of both sides, is preferable. When the resin layer is provided without an adhesive layer, a method of forming the resin layer by applying a resin composition, which is the material of the resin layer, onto the surface of the thin glass and curing the resin composition is suitably used.

[0012] In addition, the laminate of the present invention is preferably one in which the thin glass or the resin layer is disposed on the outermost surface. That is, the laminate of the present invention may be configured such that the thin glass is disposed on the outermost surface and the resin layer is disposed thereunder, or may be configured such that the resin layer is disposed on the outermost surface and the thin glass is disposed thereunder. Among them, from the viewpoint of achieving both the scratch resistance of glass and the improvement of impact resistance by the resin layer, a configuration in which the thin glass is disposed on the outermost surface and the resin layer is disposed thereunder is particularly preferred.

[0013] The resin layer preferably covers 80% or more of the area of ​​the thin glass sheet in a plan view, and more preferably covers the entire surface of the thin glass sheet.

[0014] The configurations of the first laminate and the second laminate are appropriately selected depending on the application, but when they are disposed in front of a display device such as an organic electroluminescence display device, they have the configuration shown in Fig. 1, for example. Fig. 1 is a schematic cross-sectional view showing an example of the configuration of the laminate of the present invention. In Fig. 1, the laminate 10 comprises a first resin layer 11 on one side (the viewing side) of a thin glass sheet 12, and a second resin layer 13 on the opposite side (the display device side) of the thin glass sheet 12 from the first resin layer 11 side, and may be integrated with a polarizing plate 15 by an optically transparent adhesive (OCA) 14.

[0015] The thin glass sheet is not particularly limited as long as it is plate-shaped and has a thickness of 200 μm or less. Examples of the composition of the thin glass sheet include soda-lime glass, borate glass, aluminosilicate glass, and quartz glass. In addition, according to classification based on the alkali component, the thin glass sheet may be classified as non-alkali glass or low-alkali glass. In terms of impact resistance, the thin glass sheet is preferably chemically strengthened glass that has been subjected to chemical strengthening treatment. The chemically strengthened glass preferably has a compressive stress layer formed on the surface by chemical strengthening treatment (ion exchange treatment).

[0016] The thickness of the thin glass sheet is 200 μm or less. By making the thickness of the thin glass sheet 200 μm or less, it is possible to obtain the flexibility required for a foldable electronic device. In addition, the thinner the thickness of the thin glass sheet, the more significantly the improvement in impact resistance due to the resin layer appears. The thickness of the thin glass sheet is preferably 150 μm or less, more preferably 100 μm or less. In addition, the thickness of the thin glass sheet is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. By making the thin glass sheet have a certain thickness or more, it is possible to achieve both flexibility and impact resistance.

[0017] The thin glass preferably has a light transmittance of 85% or more at a wavelength of 550 nm, and a refractive index of 1.4 to 1.65 at a wavelength of 550 nm.

[0018] The density of the thin glass is preferably 2.3 g / cm 3 ~3.0g / cm 3 and more preferably 2.3 g / cm 3 ~2.7g / cm 3 It is.

[0019] The method for producing the glass used in the thin glass sheet is not particularly limited, and for example, a mixture containing a main raw material such as silica or alumina, an antifoaming agent such as mirabilite or antimony oxide, and a reducing agent such as carbon is melted at a temperature of 1400°C to 1600°C, formed into a thin plate, and then cooled to produce the thin glass sheet. Examples of the method for forming the thin glass sheet include the slot downdraw method, the fusion method, and the float method. The glass formed into a plate by these methods may be chemically polished with a solvent such as hydrofluoric acid as necessary to make it thinner or to improve its smoothness.

[0020] In the case of chemically strengthened glass, a chemical strengthening treatment is performed. In the chemical strengthening treatment, the surface of the glass is ion-exchanged to form a surface layer (compressive stress layer) in which compressive stress remains. Specifically, alkali metal ions (typically Li ions or Na ions) with a small ionic radius present near the surface of the glass sheet are replaced by alkali ions (typically Na ions or K ions for Li ions, and K ions for Na ions) with a larger ionic radius by ion exchange at a temperature below the glass transition point. This causes compressive stress to remain on the surface of the glass, improving the strength of the glass.

[0021] As the thin glass plate, commercially available glass may be used as it is, or commercially available glass may be subjected to additional treatment such as polishing or etching to a desired thickness.

[0022] <First laminate> The resin layer has a breaking energy of 1 mJ / mm 3 The fracture energy of the resin layer is 1 mJ / mm 3By satisfying the above requirements, sufficient impact resistance can be imparted to thin glass that is thinned to realize foldable electronic devices. The breaking energy is preferably 1.5 mJ / mm 3 More preferably, it is 2 mJ / mm 3 The upper limit of the breaking energy is not particularly limited, but from the viewpoint of ensuring other properties of the laminate, it is set to, for example, 50 mJ / mm 3 The following is the result.

[0023] The measurement of the breaking energy was performed using a test piece prepared according to the following procedure in accordance with JIS K7113 "Tensile test method for plastics." A release-treated polyethylene terephthalate resin film was placed on a 0.7 mm thick glass plate with the release surface facing up, and a 0.5 mm thick silicone sheet mold punched into a dumbbell shape (SDK-400) was then placed on the plate. The resin composition used to form the resin layer was poured into the dumbbell mold, and the resin liquid was covered with the release surface of the release-treated polyethylene terephthalate resin film so as not to trap air bubbles, and then another glass plate was placed on top. Next, a test piece was placed on the plate at a wavelength of 365 nm and an illuminance of 100 mW / cm. 2 The UV LED was used as a light source and exposed to light for 15 seconds through a glass plate at 1500 mJ / cm 2 The specimen is then irradiated with ultraviolet light of 10 ...

[0024] When the fracture energy of the resin layer is measured directly from the laminate, the resin layer is punched out into a dumbbell shape (SDK-400) to be used as the test piece. Alternatively, the resin layer is dissolved in a solvent to make a resin liquid, which is then poured into the dumbbell mold and the solvent is completely dried to make the test piece.

[0025] The resin layer preferably has a Young's modulus of 1500 MPa or less. When the Young's modulus of the resin layer is 1500 MPa or less, the resin layer can have an appropriate flexibility, which is preferable for forming a laminate having the flexibility required to realize a foldable electronic device, and also, when the glass is broken, the resin film is less likely to break and a shatterproof effect can be obtained. The Young's modulus is more preferably 1300 MPa or less, and even more preferably 1200 MPa or less. In addition, the lower limit of the Young's modulus is not particularly limited, but from the viewpoint of ensuring the impact resistance of the laminate, it is preferably 50 MPa or more. The Young's modulus can be calculated by creating a stress-strain curve in the same manner as in the case of measuring the breaking energy, and determining the slope of the stress-strain curve at a strain of 0 to 10%.

[0026] The resin layer has a storage modulus of 2500 MPa or less at 25° C. When the storage modulus of the resin layer is 2500 MPa or less, sufficient impact resistance can be imparted to the thin glass. In addition, the flexibility of the resin layer can be ensured, so that a laminate having the flexibility required to realize a foldable electronic device can be obtained. The storage modulus is preferably 2000 MPa or less, more preferably 1800 MPa or less. In addition, the lower limit of the storage modulus is not particularly limited, but from the viewpoint of ensuring the impact resistance of the laminate, it is, for example, 100 MPa or more.

[0027] The storage modulus is measured by stacking two test pieces of the cured resin, prepared in the same manner as in the breaking energy measurement, to a thickness of 1 mm to prepare a measurement sample. The dynamic viscoelasticity spectrum of the prepared measurement sample is measured from -50°C to 200°C using a viscoelasticity spectrometer (e.g., DVA-200, manufactured by IT Measurement & Control Co., Ltd.) under conditions of 5°C / min and 1 Hz in a slow heating shear deformation mode, and the storage modulus at 25°C can be obtained.

[0028] <Second laminate> The resin layer has a Young's modulus of 50 MPa or more and 1500 MPa or less. The resin layer has a Young's modulus of 50 MPa or more and 1500 MPa or less, so that the resin layer can have a suitable flexibility to realize a foldable electronic device, and can impart sufficient impact resistance to the thin glass that is thinned to realize a foldable electronic device. The Young's modulus is preferably 1300 MPa or less, more preferably 1200 MPa or less, and is preferably 80 MPa or more.

[0029] The Young's modulus was measured using a test piece prepared according to the following procedure in accordance with JIS K7113 "Tensile test method for plastics." A release-treated polyethylene terephthalate resin film was placed on a 0.7 mm thick glass plate with the release surface facing up, and a 0.5 mm thick silicone sheet mold punched into a dumbbell shape (SDK-400) was placed on top. A resin composition used to form a resin layer was poured into the dumbbell mold, and the resin liquid was covered with the release surface of the release-treated polyethylene terephthalate resin film so as not to trap air bubbles, and then another glass plate was placed on top. Next, a wavelength of 365 nm and an illuminance of 100 mW / cm were measured. 2 The UV LED was used as a light source and exposed to light for 15 seconds through a glass plate at 1500 mJ / cm 2The specimen is then irradiated with ultraviolet light of 10 ...

[0030] When the Young's modulus of the resin layer is measured directly from the laminate, the resin layer is punched out into a dumbbell shape (SDK-400) to be used as the test piece. Alternatively, the resin layer is dissolved in a solvent to make a resin liquid, which is then poured into the dumbbell mold and the solvent is completely dried to make the test piece.

[0031] The resin layer has a breaking energy of 1 mJ / mm 3 The resin layer preferably has a fracture energy of 1 mJ / mm or more. 3 When the energy is more than 1.5 mJ / mm, the impact resistance of the laminate can be further improved. 3 More preferably, it is 2 mJ / mm 3 The upper limit of the breaking energy is not particularly limited, but from the viewpoint of ensuring other properties of the laminate, it is set to, for example, 50 mJ / mm 3 The breaking energy can be calculated by preparing a stress-strain curve in the same manner as in the case of measuring the Young's modulus, and determining the area surrounded by the stress-strain curve and the horizontal axis.

[0032] The resin layer preferably has a storage modulus of 2500 MPa or less at 25° C. If the storage modulus of the resin layer is 2500 MPa or less, the flexibility of the resin layer can be ensured, which is preferable for forming a laminate having the flexibility required to realize a foldable electronic device. The storage modulus is more preferably 2000 MPa or less, and even more preferably 1800 MPa or less. In addition, the lower limit of the storage modulus is not particularly limited, but is, for example, 100 MPa or more from the viewpoint of ensuring the impact resistance of the laminate.

[0033] The storage modulus is measured by stacking two test pieces of the cured resin prepared in the same manner as in the breaking energy measurement to a thickness of 1 mm to prepare a measurement sample. The dynamic viscoelasticity spectrum of the prepared measurement sample is measured from -50°C to 200°C using a viscoelasticity spectrometer (e.g., DVA-200, manufactured by IT Measurement & Control Co., Ltd.) under conditions of 5°C / min and 1 Hz in a slow heating shear deformation mode, and the storage modulus at 20°C can be obtained.

[0034] <First and second laminates> The resin layer preferably has a breaking elongation of 5% or more. When the breaking elongation of the resin layer is 5% or more, cracks and whitening are unlikely to occur in a bending durability test. The breaking elongation of the resin layer is more preferably 7% or more. There is no particular upper limit to the breaking elongation, but from the viewpoint of ensuring the impact resistance of the laminate, it is preferably 1000% or less. The breaking elongation can be determined by performing a tensile test in the same manner as in the measurement of the breaking energy, and using the value of the strain when the test piece breaks.

[0035] The resin layer preferably has a breaking strength of 5 MPa or more and 50 MPa or less. When the breaking strength of the resin layer is in the range of 5 MPa or more and 50 MPa or less, it is easy to impart sufficient impact resistance to the thin glass. The breaking strength of the resin layer is more preferably 10 MPa or more and 40 MPa or less. The breaking strength can be measured by performing a tensile test in the same manner as in the measurement of the breaking energy, and using the value of the stress when the test piece breaks.

[0036] The resin layer preferably has a glass transition temperature of 100° C. or less. When the glass transition temperature of the resin layer is 100° C. or less, the flexibility of the resin layer can be ensured, which is preferable in terms of forming a laminate having the flexibility required to realize a foldable electronic device. The glass transition temperature is more preferably 80° C. or less. The lower limit of the glass transition temperature is not particularly limited, but is, for example, 0° C. or more from the viewpoint of ensuring other properties of the laminate. The glass transition temperature can be determined by creating a dynamic viscoelasticity spectrum in the same manner as in the case of measuring the storage modulus, and using the temperature at the maximum value of the loss tangent.

[0037] The resin layer preferably has a total light transmittance of 80% or more. If the resin layer has a total light transmittance of 80% or more, the transparency of the resin layer can be ensured, which is preferable for forming a laminate having the transparency required to realize a foldable display device (foldable display). The total light transmittance is more preferably 90% or more. The total light transmittance can be measured, for example, using a HazeMeter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.). The total light transmittance is measured by a method conforming to JIS K 7361-1.

[0038] The thickness of the resin layer is 5 μm or more. By having a thickness of 5 μm or more, the flexible resin layer can exhibit a function of absorbing impact, and can impart sufficient impact resistance to thin glass that has been thinned to realize a foldable electronic device. The thickness of the resin layer is preferably 10 μm or more. In addition, the upper limit of the thickness of the resin layer is not particularly limited, but from the viewpoint of ensuring the foldability of the laminate, it is preferably thinner than thin glass, specifically, it is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less.

[0039] In addition, a preferred embodiment of the first laminate and the second laminate includes a thin glass having a thickness of 200 μm or less, a first resin layer having a thickness of 5 μm or more arranged on one side of the thin glass, and a second resin layer having a thickness of 5 μm or more arranged on the opposite side of the thin glass from the first resin layer. At least one layer of the first resin layer and the second resin layer may be provided in the first laminate and the second laminate. In the preferred embodiment, the first laminate and the second laminate may have another layer other than the thin glass, the first resin layer, and the second resin layer. For example, the first resin layer and the second resin layer may be laminated with the thin glass via an adhesive layer, but it is preferable that they are in direct contact with the thin glass without an adhesive layer. When the first resin layer and the second resin layer are provided without an adhesive layer, a method of forming a resin layer by applying a resin composition that is the material for the first resin layer and the second resin layer onto the surface of the thin glass and curing the resin composition is preferably used.

[0040] The first resin layer and the second resin layer preferably cover 80% or more of the area of ​​the thin glass sheet in a plan view, and more preferably cover the entire surface of the thin glass sheet.

[0041] <Characteristics of the first and second resin layers of the first laminate> In the first laminate, the first resin layer and the second resin layer each have a breaking energy of 1 mJ / mm 3 It is preferable that the storage modulus at 25° C. is 2500 MPa or less. 3 By satisfying the above requirements, sufficient impact resistance can be imparted to thin glass that is thinned to realize foldable electronic devices. The breaking energy is more preferably 1.5 mJ / mm 3 More preferably, it is 2 mJ / mm 3 The upper limit of the breaking energy is not particularly limited, but from the viewpoint of ensuring other properties of the laminate, it is set to, for example, 50 mJ / mm 3The storage modulus is 2500 MPa or less. If the storage modulus is 2500 MPa or less, sufficient impact resistance can be imparted to the thin glass. Since the flexibility of the resin layer can be ensured, a laminate having the flexibility required to realize a foldable electronic device can be obtained. The storage modulus is more preferably 2000 MPa or less, and even more preferably 1800 MPa or less. The lower limit of the storage modulus is not particularly limited, but is, for example, 100 MPa or more from the viewpoint of ensuring the impact resistance of the laminate.

[0042] The breaking energy can be measured in accordance with JIS K7113 "Tensile test method for plastics" using a test piece prepared according to the following procedure. A release-treated polyethylene terephthalate resin film is placed on a 0.7 mm thick glass plate with the release surface facing up, and a 0.5 mm thick silicone sheet mold punched into a dumbbell shape (SDK-400) is then placed on top. The resin composition used to form the resin layer is poured into the dumbbell shape, and the resin liquid is covered with the release surface of the release-treated polyethylene terephthalate resin film to avoid trapping air bubbles, and then another glass plate is placed on top. Next, a wavelength of 365 nm and an illuminance of 100 mW / cm2 are applied. 2 The UV LED was used as a light source and exposed to light for 15 seconds through a glass plate at 1500 mJ / cm 2 The specimen is then irradiated with ultraviolet light of 10 ...

[0043] When the fracture energy of the resin layer is measured directly from the laminate, the resin layer is punched out into a dumbbell shape (SDK-400) to be used as the test piece. Alternatively, the resin layer is dissolved in a solvent to make a resin liquid, which is then poured into the dumbbell mold and the solvent is completely dried to make the test piece.

[0044] The storage modulus is measured by preparing a measurement sample in the same manner as in the measurement of the breaking energy, except that a 0.5 mm thick silicon sheet mold punched into a rectangular shape with a width of 5 mm and a length of 50 mm is used instead of a 0.5 mm thick silicon sheet mold punched into a dumbbell shape (SDK-400). The dynamic viscoelasticity spectrum of the prepared measurement sample is measured from -50°C to 200°C using a viscoelasticity spectrometer (e.g., DVA-200 manufactured by IT Measurement & Control Co., Ltd.) under conditions of 5°C / min and 1Hz in a slow heating shear deformation mode, and the storage modulus at 25°C can be obtained.

[0045] The first resin layer and the second resin layer preferably have a Young's modulus of 1500 MPa or less. When the Young's modulus is 1500 MPa or less, the first resin layer and the second resin layer can have an appropriate flexibility, which is preferable for forming a laminate having the flexibility required to realize a foldable electronic device, and also, when the glass is broken, the resin layer is less likely to break and a shatterproof effect can be obtained. The Young's modulus is more preferably 1400 MPa or less, and even more preferably 1300 MPa or less. In addition, the lower limit of the Young's modulus is not particularly limited, but from the viewpoint of ensuring the impact resistance of the laminate, it is preferably 50 MPa or more. The Young's modulus can be calculated by creating a stress-strain curve in the same manner as in the case of measuring the breaking energy, and determining the slope of the stress-strain curve at a strain of 0 to 10%.

[0046] <Characteristics of the first and second resin layers of the second laminate> In the second laminate, the first resin layer and the second resin layer each preferably have a Young's modulus of 50 MPa or more and 1500 MPa or less. By having the Young's modulus of 50 MPa or more and 1500 MPa or less, appropriate flexibility for realizing a foldable electronic device can be obtained, and sufficient impact resistance can be imparted to a thin glass that is thinned to realize a foldable electronic device. The Young's modulus is more preferably 1400 MPa or less, even more preferably 1300 MPa or less, and more preferably 80 MPa or more.

[0047] The first resin layer and the second resin layer each have a breaking energy of 1 mJ / mm 3 It is preferable that the breaking energy is 1 mJ / mm or more. 3 When the energy is more than 1.5 mJ / mm, the impact resistance of the laminate can be further improved. 3 More preferably, it is 2 mJ / mm 3 The upper limit of the breaking energy is not particularly limited, but from the viewpoint of ensuring other properties of the laminate, it is set to, for example, 50 mJ / mm 3 The following is the result.

[0048] At least one of the first resin layer and the second resin layer has a storage modulus at 25°C of 3000 MPa or less, more preferably 2500 MPa or less, even more preferably 2000 MPa or less, particularly preferably 1800 MPa or less, and particularly preferably 1500 MPa or less. By setting the storage modulus within the above range, the flexibility of the resin layer can be improved, which is preferable in terms of forming a laminate having the flexibility required to realize a foldable electronic device. In addition, the lower limit of the storage modulus is not particularly limited, but from the viewpoint of ensuring the impact resistance of the laminate, it is preferably 10 MPa or more, more preferably 100 MPa or more, and even more preferably 500 MPa or more. From the viewpoint of improving the foldability of the laminate, it is preferable that both the first resin layer and the second resin layer have a storage modulus at 25°C of 2500 MPa or less. From the viewpoint of ensuring the impact resistance of the laminate, it is preferable that both the first resin layer and the second resin layer have a storage modulus at 25°C of 100 MPa or more.

[0049] <Characteristics of the first and second resin layers common to the first and second laminates> The first resin layer and the second resin layer each preferably have a breaking elongation of 5% or more. When the breaking elongation is 5% or more, cracks and whitening are unlikely to occur in a bending durability test. The breaking elongation is more preferably 7% or more. There is no particular upper limit to the breaking elongation, but from the viewpoint of ensuring the impact resistance of the laminate, it is preferably 1000% or less. The breaking elongation can be determined by performing a tensile test in the same manner as in the measurement of the breaking energy, and using the value of the strain when the test piece breaks.

[0050] The first resin layer and the second resin layer each preferably have a breaking strength of 5 MPa or more and 50 MPa or less. When the breaking strength is in the range of 5 MPa or more and 50 MPa or less, it is easy to impart sufficient impact resistance to the thin glass. The breaking strength is more preferably 10 MPa or more and 40 MPa or less. The breaking strength can be measured by performing a tensile test in the same manner as in the measurement of the breaking energy, and using the value of the stress when the test piece breaks.

[0051] The first resin layer and the second resin layer each preferably have a glass transition temperature of 100° C. or less, and at least one of the first resin layer and the second resin layer preferably has a glass transition temperature of 100° C. or less. When the glass transition temperature of the resin layer is 100° C. or less, the flexibility of the resin layer can be ensured, which is preferable in terms of forming a laminate having the flexibility required to realize a foldable electronic device. The glass transition temperature is more preferably 80° C. or less, and even more preferably 60° C. or less. In addition, the lower limit of the glass transition temperature is not particularly limited, but is, for example, 0° C. or more from the viewpoint of ensuring other properties of the laminate. The glass transition temperature can be determined by creating a dynamic viscoelasticity spectrum in the same manner as in the case of measuring the storage modulus, and using the temperature at the maximum value of the loss tangent.

[0052] The first resin layer and the second resin layer each preferably have a total light transmittance of 80% or more. If the total light transmittance of the resin layer is 80% or more, the transparency of the resin layer can be ensured, which is preferable for forming a laminate having the transparency required to realize a foldable display device (foldable display). The total light transmittance is more preferably 90% or more. The total light transmittance can be measured, for example, using a HazeMeter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.). The total light transmittance is measured by a method conforming to JIS K 7361-1.

[0053] The thickness of each of the first resin layer and the second resin layer is preferably 5 μm or more. By having a thickness of the resin layer of 5 μm or more, the flexible resin layer can exhibit a function of absorbing impact, and sufficient impact resistance can be imparted to the thin glass that has been thinned to realize a foldable electronic device. The thickness of the first resin layer and the second resin layer is more preferably 10 μm or more. In addition, the upper limit of the thickness of the first resin layer and the second resin layer is not particularly limited, but from the viewpoint of ensuring the foldability of the laminate, it is preferable that it is thinner than thin glass, specifically, it is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and most preferably 20 μm or less. From the viewpoint of ensuring the foldability of the laminate, it is preferable that at least one of the first resin layer and the second resin layer has a thickness of 25 μm or less.

[0054] Hereinafter, each material that can be used for the resin layer, the first resin layer, and the second resin layer will be described. The resin composition used to form the resin layer, the first resin layer, and the second resin layer is not particularly limited as long as it can adjust the properties of the resin layer obtained after curing within a desired range, but for example, a resin composition containing a cationic curable resin is preferably used because it has excellent adhesion to glass. At least one of the first resin layer and the second resin layer preferably contains a cationic curable resin polymer, and it is more preferable that both the first resin layer and the second resin layer contain a cationic curable resin polymer.

[0055] The above-mentioned cationically curable resin is not particularly limited as long as it is a compound having at least one cationically polymerizable functional group in the molecule and having high cationically polymerizable properties. Examples of the cationic polymerizable functional group include an epoxy group, an oxetanyl group, a vinyl ether group, an episulfide group, and an ethyleneimine group. Among them, the cationic curable resin preferably contains at least one resin selected from the group consisting of an epoxy resin (an epoxy group-containing compound), an oxetane resin (an oxetanyl group-containing compound), and a vinyl ether resin (a vinyl ether group-containing compound), and more preferably contains an epoxy resin (an epoxy group-containing compound) and an oxetane resin (an oxetanyl group-containing compound). The epoxy resin and the oxetane resin have excellent adhesion to the thin glass sheet, and therefore can suppress peeling of the resin layer when the laminate of the present invention is repeatedly folded.

[0056] The epoxy resin (epoxy group-containing compound) is not particularly limited, and examples thereof include bisphenol-type epoxy resins such as bisphenol A type, bisphenol F type, bisphenol AD ​​type, and bisphenol S type; novolac-type epoxy resins such as phenol novolac type and cresol novolac type; aromatic epoxy resins such as resorcinol-type epoxy resins and trisphenolmethane triglycidyl ether; alicyclic epoxy resins; naphthalene-type epoxy resins; fluorene-type epoxy resins; dicyclopentadiene-type epoxy resins; polyether-modified epoxy resins such as epoxy resins having a polyether skeleton; NBR-modified epoxy resins; CTBN-modified epoxy resins; and hydrogenated products thereof. Among them, hydrogenated bisphenol-type epoxy resins and epoxy resins having a polyether skeleton are preferably used. These epoxy resins may be used alone or in combination of two or more.

[0057] The hydrogenated bisphenol type epoxy resin is preferably a hydrogenated bisphenol A type epoxy resin containing a hydrogenated bisphenol A skeleton. The hydrogenated bisphenol type epoxy resin may be a multimer such as a dimer. The hydrogenated bisphenol type epoxy resin preferably has an epoxy equivalent of 100 or more and 2000 or less. By having the epoxy equivalent of 100 or more and 2000 or less, the crosslinking density of the epoxy resin is controlled within a preferred range, and the impact resistance can be further improved. The epoxy equivalent is defined as "the mass of a resin containing one equivalent of an epoxy group" and is measured by a method in accordance with JIS K7236.

[0058] Examples of the alicyclic epoxy resin include 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, ε-caprolactone-modified 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, bis(3,4-epoxycyclohexyl)adipate, 1,2-epoxy-4-vinylcyclohexane, 1,4-cyclohexanedimethanol diglycidyl ether, epoxyethyldivinylcyclohexane, diepoxyvinylcyclohexane, 1,2,4-triepoxyethylcyclohexane, limonene dioxide, and alicyclic epoxy group-containing silicone oligomers. These alicyclic epoxy resins may be used alone or in combination of two or more.

[0059] The epoxy resin may be an epoxy resin that is liquid at room temperature (23° C.) or may be an epoxy resin that is solid at room temperature, or may be used in appropriate combination. The epoxy resin preferably contains at least one epoxy resin that is liquid at room temperature, and for example, a hydrogenated bisphenol type epoxy resin that is liquid at room temperature or an epoxy resin having a polyether skeleton that is liquid at room temperature is preferably used. Examples of the epoxy resins that are liquid at room temperature include polyether skeleton epoxy resins such as "jER YX7400" and "jER YX7400N" (both manufactured by Mitsubishi Chemical Corporation); bisphenol A type epoxy resins such as "EPICLON 840", "EPICLON 840-S", "EPICLON 850", "EPICLON 850-S", and "EPICLON EXA-850CRP" (both manufactured by DIC Corporation); bisphenol F type epoxy resins such as "EPICLON 830", "EPICLON 830-S", "EPICLON EXA-830CRP", and "EPICLON EXA-830LVP" (both manufactured by DIC Corporation) and "jER 806H" (manufactured by Mitsubishi Chemical Corporation); naphthalene type epoxy resins such as "EPICLON HP-4032" and "EPICLON HP-4032D" (both manufactured by DIC Corporation); "jER YX8000" and "jER Hydrogenated bisphenol A type epoxy resins such as "YX8034", "jER YX8040" (all manufactured by Mitsubishi Chemical Corporation), "EPICLON EXA-7015" (manufactured by DIC Corporation), and "EX-252" (manufactured by Nagase ChemteX Corporation); resorcinol type epoxy resins such as "EX-201" (manufactured by Nagase ChemteX Corporation); "Celloxide 2081", "Celloxide 2021P", "Celloxide 2000", "Celloxide 3000", "Celloxide 8000", "Celloxide 8010", "EHPE3150" (all manufactured by Daicel Corporation), "TTA21" (manufactured by Jiangsu TetraChem Co., Ltd.), and "Rikaresin" Alicyclic epoxy resins such as "DME-100" (manufactured by New Japan Chemical Co., Ltd.), "X-40-2670", "X-22-169AS", and "X-22-169B" (manufactured by Shin-Etsu Chemical Co., Ltd.) are commercially available.

[0060] Examples of the epoxy resins that are solid at room temperature include bisphenol A type epoxy resins such as "EPICLON 860", "EPICLON 10550", and "EPICLON 1055" (all manufactured by DIC Corporation); bisphenol F type epoxy resins such as "jER 4005P" (manufactured by Mitsubishi Chemical Corporation); bisphenol S type epoxy resins such as "EPICLON EXA-1514" (manufactured by DIC Corporation); naphthalene type epoxy resins such as "EPICLON HP-4700", "EPICLON HP-4710", and "EPICLON HP-4770" (all manufactured by DIC Corporation); dicyclopentadiene type epoxy resins such as "EPICLON HP-7200 series" (manufactured by DIC Corporation); and cresol novolac type epoxy resins such as "EPICLON HP-5000" and "EPICLON EXA-9900" (all manufactured by DIC Corporation).

[0061] The oxetane resin (oxetanyl group-containing compound) which is the cationic curable resin is not particularly limited, and examples thereof include 3-ethyl-3-[(2-ethylhexyloxy)methyl]oxetane, 3-ethyl-3-hydroxymethyloxetane, 1,4-bis([(3-ethyl-3-oxetanyl)methoxy]methyl)benzene, 3-ethyl-3-(phenoxymethyl)oxetane, bis[(3-ethyloxetan-3-yl)methyl]ether, 3-ethyl-3-([3-(triethoxysilyl)propoxy]methyl)oxetane, and oxetanylsilsesquioxane. As the oxetane resin, a monofunctional one is preferably used. As the oxetane resin, for example, "ETRENACOLL EHO" (manufactured by Ube Industries, Ltd.), "ARON OXT-101", "ARON OXT-121", "ARON OXT-211", "ARON OXT-221", "ARON OXT-610" (all manufactured by Toagosei Co., Ltd.) and the like are commercially available. These can be used alone or in combination of two or more.

[0062] The vinyl ether resin (vinyl ether group-containing compound) which is the cationically curable resin is not particularly limited, and examples thereof include methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, allyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, n-pentyl vinyl ether, isopentyl vinyl ether, tert-pentyl vinyl ether, n-hexyl vinyl ether, isohexyl vinyl ether, 2-ethylhexyl vinyl ether, n-heptyl vinyl ether, n-octyl vinyl ether, nonyl vinyl ether, decyl vinyl ether, dodecyl vinyl ether, hexadecyl vinyl ether, octadecyl vinyl ether, ethoxymethyl vinyl ether, 2-methoxyethyl vinyl ether, 2-ethoxyethyl vinyl ether, 2-butoxyethyl vinyl ether, acetoxymethyl vinyl ether, 2-acetoxyethyl vinyl ether, 3-acetoxypropyl vinyl ether, 4-acetoxybutyl vinyl ether, 4-ethoxybutyl ... -(2-methoxyethoxy)ethyl vinyl ether, 3-hydroxypropyl vinyl ether, 4-hydroxybutyl vinyl ether, 5-hydroxypentyl vinyl ether, 6-hydroxyhexyl vinyl ether, diethylene glycol monovinyl ether, diethylene glycol methyl vinyl ether, diethylene glycol ethyl vinyl ether, triethylene glycol monovinyl ether, tetraethylene glycol monovinyl ether, polyethylene glycol monovinyl ether, propylene glycol monovinyl ether, dipropylene glycol monovinyl ether, tripropylene glycol monovinyl ether, polypropylene glycol monovinyl ether, 4-hydroxycyclohexyl vinyl ether, cyclohexyl dimethanol monovinyl ether, trimethylolpropane monovinyl ether, ethylene oxide-added trimethylolpropane monovinyl ether, pentaerythritol monovinyl ether, ethylene oxide-added pentaerythritol monovinyl ether, cyclohexyl vinyl ether, cyclohexyl methyl vinyl ether,Cyclohexyl ethyl vinyl ether, menthyl vinyl ether, tetrahydrofurfuryl vinyl ether, norbornenyl vinyl ether, 1-adamantyl vinyl ether, 2-adamantyl vinyl ether, phenyl vinyl ether, benzyl vinyl ether, 1-naphthyl vinyl ether, 2-naphthyl vinyl ether, glycidyl vinyl ether, diethylene glycol ethyl vinyl ether, triethylene glycol methyl vinyl ether, divinyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, tetraethylene glycol divinyl ether, polyethylene glycol divinyl ether, propylene glycol divinyl ether, dipropylene glycol divinyl ether, tripropylene glycol divinyl ether, polypropylene glycol divinyl ether, butanediol divinyl ether, neopentyl glycol divinyl Examples of the vinyl ether include vinyl ether, hexanediol divinyl ether, nonanediol divinyl ether, hydroquinone divinyl ether, 1,4-cyclohexanediol divinyl ether, 1,4-cyclohexanedimethanol divinyl ether, trimethylolpropane divinyl ether, ethylene oxide-added trimethylolpropane divinyl ether, pentaerythritol divinyl ether, ethylene oxide-added pentaerythritol divinyl ether, trimethylolpropane trivinyl ether, ethylene oxide-added trimethylolpropane trivinyl ether, pentaerythritol trivinyl ether, ethylene oxide-added pentaerythritol trivinyl ether, pentaerythritol tetravinyl ether, ethylene oxide-added pentaerythritol tetravinyl ether, ditrimethylolpropane tetravinyl ether, and dipentaerythritol hexavinyl ether. These may be used alone or in combination of two or more.

[0063] The cationic curable resin is preferably a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, or a compound containing an oxetanyl group. Such cationic curable resins can provide particularly excellent impact resistance, and therefore provide good results in the evaluation of shatterproofness by the pen drop test.

[0064] The content of the hydrogenated bisphenol type epoxy resin is not particularly limited, but is preferably 20% by weight or more, more preferably 40% by weight or more, and is preferably 70% by weight or less, and more preferably 50% by weight or less, based on the total amount of the resin layer containing the cationic curable resin polymer. The content of the epoxy resin having the polyether skeleton is not particularly limited, but is preferably 10% by weight or more, more preferably 12% by weight or more, and is preferably 40% by weight or less, more preferably 30% by weight or less, and even more preferably 20% by weight or less, based on the total amount of the resin layer containing the cationic curable resin polymer. The content of the oxetanyl group-containing compound is not particularly limited, but is preferably 10% by weight or more, more preferably 20% by weight or more, and is preferably 70% by weight or less, more preferably 60% by weight or less, and even more preferably 50% by weight or less, based on the total amount of the resin layer containing the cationic curable resin polymer. It is preferable that the content of the hydrogenated bisphenol type epoxy resin in the resin layer containing the polymer of the cationic curable resin is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less.

[0065] The resin composition preferably contains a polymerization initiator. The polymerization initiator may be a photopolymerization initiator or a thermal polymerization initiator. Examples of the photopolymerization initiator include compounds consisting of a combination of a cation such as diphenyliodonium, 4-methoxydiphenyliodonium, bis(4-methylphenyl)iodonium, bis(4-tert-butylphenyl)iodonium, bis(dodecylphenyl)iodonium, diphenyl-4-thiophenoxyphenylsulfonium, bis[4-(diphenylsulfonio)-phenyl]sulfide, bis[4-(di(4-(2-hydroxyethyl)phenyl)sulfonio)-phenyl]sulfide, η5-2,4-(cyclopentadienyl)[1,2,3,4,5,6-η-(methylethyl)benzene]-iron(1+) and an anion such as tetrafluoroborate, hexafluorophosphate, triphenylhexafluorophosphate, and hexafluoroarsenate. Examples of the thermal polymerization initiator include imidazoles, quaternary ammonium salts, phosphorus compounds, amines, phosphines, phosphonium salts, bicyclic amidines and their salts, acid anhydrides, novolac-type phenolic resins obtained by condensation reaction of phenol, cresol, xylenol, resorcin, or the like with formaldehyde, polymercapto resins such as liquid polymercaptan and polysulfide, amides, etc. These polymerization initiators may be used alone or in combination of two or more kinds.

[0066] The content of the polymerization initiator is preferably 0.1 parts by weight at the lower limit and 10 parts by weight at the upper limit with respect to 100 parts by weight of the cationic curable resin. If the content of the polymerization initiator is less than 0.1 parts by weight, the cationic polymerization may not proceed sufficiently or the curing reaction may be too slow. If the content of the polymerization initiator is more than 10 parts by weight, the curing reaction of the resin composition may be too fast, resulting in reduced workability and non-uniform composition of the obtained resin layer. The more preferred lower limit of the content of the polymerization initiator is 0.5 parts by weight and the more preferred upper limit is 5 parts by weight.

[0067] The above resin composition may further contain various known additives such as a solvent, a viscosity adjuster, a surface modifier (surfactant, leveling agent), a plasticizer, a silane coupling agent, a tackifier, a sensitizer, a thermosetting agent, a crosslinking agent, a cure retarder, an antioxidant, a storage stabilizer, a dispersant, and a filler, within the scope not impairing the object of the present invention.

[0068] The method for preparing the resin composition is not particularly limited, and examples thereof include a method of mixing a curable resin, a polymerization initiator, and additives to be added as necessary using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.

[0069] The method for forming the resin layer, the first resin layer, and the second resin layer is not particularly limited, and for example, they can be formed by applying a resin composition onto the surface of the thin glass plate, and then curing the composition by light irradiation, heating, etc. The method for applying the resin composition is not particularly limited, and for example, a screen printing method, a die coat printing method, an offset printing method, a gravure printing method, an inkjet printing method, etc. may be used.

[0070] In addition, an electronic device comprising the laminate of the present invention is also one aspect of the present invention. As the electronic device of the present invention, a foldable electronic device (foldable electronic device) is preferable, and among them, a foldable display device (foldable display) is preferable. Specifically, for example, a mobile display terminal such as a smartphone, an electronic book, or a tablet PC can be mentioned. In a display device comprising the first laminate or the second laminate, it is preferable that the first resin layer is arranged on the viewing side and the second resin layer is arranged on the display device side.

[0071] The present invention also relates to a cover glass comprising the laminate of the present invention. The cover glass of the present invention is preferably a protective glass arranged to cover an article to be protected, and more preferably a display cover glass in which the article to be protected is a display device.

[0072] Furthermore, the resin composition used to form the resin layer of the laminate of the present invention also constitutes the present invention. The resin composition of the present invention can exhibit excellent impact resistance after curing, and is suitable for forming a thin film for protecting an adherend such as glass.

[0073] The composition of the resin composition of the present invention is the same as that of the resin composition used for forming the resin layer, the first resin layer, and the second resin layer. The resin composition of the present invention preferably contains a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, and an oxetanyl group-containing compound. Such a resin composition can provide particularly excellent impact resistance, and therefore provides good results in the evaluation of shatterproofness by a pen drop test.

[0074] The hydrogenated bisphenol type epoxy resin is preferably a hydrogenated bisphenol A type epoxy resin containing a hydrogenated bisphenol A skeleton. The hydrogenated bisphenol type epoxy resin may be a multimer such as a dimer. The hydrogenated bisphenol type epoxy resin preferably has an epoxy equivalent of 100 or more and 2000 or less. The hydrogenated bisphenol type epoxy resin is preferably liquid at room temperature (23°C). The hydrogenated bisphenol type epoxy resin may be used alone or in combination of two or more kinds. The epoxy resin having a polyether skeleton is preferably one that is liquid at room temperature (23° C.) The epoxy resin having a polyether skeleton may be used alone or in combination of two or more kinds. As the oxetanyl group-containing compound (oxetane resin), a monofunctional compound is preferably used. The oxetanyl group-containing compound may be used alone or in combination of two or more kinds.

[0075] The content of the hydrogenated bisphenol epoxy resin is not particularly limited, but is preferably 20% by weight or more, more preferably 40% by weight or more, and is preferably 70% by weight or less, and more preferably 50% by weight or less, based on the total amount of the resin composition of the present invention. The content of the epoxy resin having a polyether skeleton is not particularly limited, but is preferably 10% by weight or more, more preferably 12% by weight or more, and is preferably 40% by weight or less, more preferably 30% by weight or less, and even more preferably 20% by weight or less, based on the total amount of the resin composition of the present invention. The content of the oxetanyl group-containing compound is not particularly limited, but is preferably 10% by weight or more, more preferably 20% by weight or more, and is preferably 70% by weight or less, more preferably 60% by weight or less, and even more preferably 50% by weight or less, based on the total amount of the resin composition of the present invention. It is preferred that the content of the hydrogenated bisphenol type epoxy resin in the resin composition of the present invention is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less.

[0076] The above-mentioned resin composition is preferably a resin composition used for coating a thin glass sheet having a thickness of 200 μm or less.

[0077] The resin composition may contain a solvent from the viewpoint of coatability and the like. As the solvent, from the viewpoint of coatability, storage stability, and the like, a non-polar solvent having a boiling point of 200° C. or less or an aprotic polar solvent having a boiling point of 200° C. or less is preferable. Examples of the non-polar solvent having a boiling point of 200° C. or less or an aprotic polar solvent having a boiling point of 200° C. or less include ketone-based solvents, ester-based solvents, hydrocarbon-based solvents, halogen-based solvents, ether-based solvents, and nitrogen-containing solvents. From the viewpoint of the stability of the coating liquid, the uniformity of the coating film, drying efficiency, and the like, the boiling point of the non-polar solvent or aprotic polar solvent is more preferably in the range of 80° C. to 180° C.

[0078] The resin composition preferably has a viscosity of 1 to 1000 mPa·s at 25°C as measured using an E-type viscometer. A more preferred range of the viscosity is adjusted depending on the coating method. For example, a range of 5 to 50 mPa·s is preferred for coating by the inkjet method, a range of 10 to 100 mPa·s is preferred for coating by the slit coating method, and a range of 100 to 1000 mPa·s is preferred for coating by the roll coating method or offset printing method. On the other hand, if the viscosity exceeds 1000 mPa·s, the leveling property of the coating liquid decreases, and the uniformity of the thickness of the coating film tends to decrease. The viscosity can be measured, for example, by using a VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer and selecting an appropriate rotation speed of 1 to 100 rpm from the optimum torque number in each viscosity range with a cone plate of CP1. Effect of the Invention

[0079] According to the present invention, it is possible to provide a laminate having excellent impact resistance. In addition, according to the present invention, it is possible to provide an electronic device and a cover glass using the laminate, and a resin composition used for forming a resin layer of the laminate. [Brief description of the drawings]

[0080] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0082] (Examples 1 to 12, Comparative Examples 1 to 3) According to the compounding ratios shown in Table 1 below, the curable resin shown in (1), the initiator shown in (2), and the surface modifier shown in (3) were mixed by stirring to obtain a resin composition. The obtained resin composition was diluted with a solvent, propylene glycol monomethyl ether acetate, to adjust the viscosity, and applied to a thin glass plate having a thickness of 50 μm so as to have a thickness of 10 μm after drying. The obtained coating film was dried at a temperature of 100° C. for 15 minutes, and then irradiated with ultraviolet light having a wavelength of 365 nm at a dose of 1500 mJ / cm. 2 The resin was then cured by irradiation with light at 80° C. for 30 minutes, and then heated at 80° C. As a result, a laminate was obtained in which a resin layer made of a cured resin was formed on one side of the thin glass sheet.

[0083] (1) Curing resin EPICLON EXA-830LVP (a mixture of bisphenol F liquid epoxy resin and bisphenol A liquid epoxy resin, manufactured by DIC) jER YX7400 (polyether-based liquid epoxy resin, manufactured by Mitsubishi Chemical Corporation) jER 4005P (Bisphenol F type solid epoxy resin, manufactured by Mitsubishi Chemical Corporation) jER 806H (bisphenol F type liquid epoxy resin, manufactured by Mitsubishi Chemical Corporation) jER YX8000 (hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 192~220) jER YX8034 (hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 250~360) jER YX8040 (hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 900~1500) Celloxide 2021P (3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, manufactured by Daicel Corporation) ETRENACOLL EHO (3-ethyl-3-hydroxymethyloxetane, manufactured by Ube Industries)

[0084] (2) Initiator CPI-210S (a triarylsulfonium salt type photocationic polymerization initiator, manufactured by San-Apro Co., Ltd.)

[0085] (3) Surface modifier JAR-33 (organically modified polysiloxane, manufactured by Jujo Chemical Co., Ltd.)

[0086] Comparative Example 4 The thin glass sheet of Comparative Example 4 was the same 50 μm thick thin glass sheet as those of Examples 1 to 5 and Comparative Examples 1 to 3, on whose surface no resin layer was formed.

[0087] <Physical property measurements> The physical properties of the cured resin products prepared using the resin compositions of Examples 1 to 12 and Comparative Examples 1 to 3 were measured by the following methods. The results are shown in Table 1.

[0088] (Storage modulus and glass transition temperature) Test pieces of the cured resin were laminated to a thickness of 1 mm to prepare a measurement sample. The dynamic viscoelasticity spectrum of the prepared measurement sample was measured from -50°C to 200°C using a viscoelasticity spectrometer (IT Measurement and Control Co., Ltd., DVA-200) under conditions of a slow heating rate shear deformation mode of 5°C / min and 1 Hz. From the obtained dynamic viscoelasticity spectrum, the storage modulus at 25°C was calculated. The temperature at the maximum value of the loss tangent was taken as the glass transition temperature Tg (°C).

[0089] (Young's modulus, breaking elongation, breaking strength, breaking energy) In accordance with JIS K7113 "Tensile test method for plastics", a 0.5 mm thick dumbbell-shaped (SDK-400) test piece of the cured resin was prepared and a tensile test was performed using a tensile tester. The tensile test was performed until the test piece broke, with a chuck distance of 20 mm, a tensile speed of 50 mm / min, and a sampling interval of 20 μm. From the obtained measurement results, a stress-strain curve was created with stress (unit: MPa) on the vertical axis and strain (unit: %) on the horizontal axis. The value of strain when the test piece broke was taken as the breaking elongation, and the value of maximum stress when the test piece broke was taken as the breaking strength. Young's modulus was calculated by determining the slope of the stress-strain curve at strains of 0 to 10%. The breaking energy was calculated by determining the area surrounded by the stress-strain curve and the horizontal axis.

[0090] <Evaluation> The following evaluations were carried out on the laminates obtained in Examples 1 to 12 and Comparative Examples 1 to 3, and the thin glass sheet of Comparative Example 4. The results are shown in Table 1.

[0091] (Total light transmittance and haze) The total light transmittance and haze were measured using a HazeMeter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.).

[0092] (Pen Drop Test) The laminate was placed on a 10 mm thick SUS plate with the thin glass side facing up, and a ballpoint pen (manufactured by BIC Japan, orange EG0.7, nib 0.7 mmφ, weight 5.75 g) was dropped vertically from a specified height onto the glass surface of the laminate with the nib facing downwards. The maximum height at which no cracks occurred in the thin glass was recorded as the test result.

[0093] (Shatterproof test) For the laminates in which cracks occurred in the thin glass sheets in the above-mentioned pen drop test, shatterproofness was evaluated based on the following evaluation criteria. ◯: Cracks occurred in the glass, but the glass fragmented by the cracks was held together by the resin layer, and there was no peeling between the resin layer and the thin glass sheet, so no glass shattering was observed. ×: A crack occurred in the thin glass sheet and simultaneously a crack occurred in the resin layer, causing the glass to fragment, or the resin layer and the thin glass sheet peeled off, causing the glass to fragment.

[0094] (Bending durability test) Using a U-shaped bending tester (Yuasa System Co., Ltd., DLDMLH-FS), the laminate was bent so that the thin glass was placed on the inside, and repeatedly bent at a test speed of 2 seconds / time, a bending radius R of 3.0 mm, and 100,000 times. Then, the laminate was placed on a horizontal movable plate, and the two movable plates were rotated 90 degrees to bend the laminate into a U-shape. After the test, the appearance of the laminate was visually confirmed. The laminate was evaluated as "○○" when there was no change in appearance before and after the test, as "○" when cracks or whitening occurred at the ends after the test but not other than the ends, and as "×" when cracks or whitening occurred other than the ends and the appearance changed after the test.

[0095] [Table 1]

[0096] (Examples 13 to 25) According to the compounding ratio shown in Table 2 below, a curable resin shown in (1), an initiator shown in (2), and a surface modifier shown in (3) were mixed and stirred to obtain a resin composition. The obtained resin composition was diluted with a solvent, propylene glycol monomethyl ether acetate, to adjust the viscosity, and applied to a thin glass plate having a thickness of 50 μm so as to have a thickness after drying shown in Table 2 below. The obtained coating film was dried at a temperature of 100° C. for 15 minutes, and then irradiated with ultraviolet light having a wavelength of 365 nm at a dose of 1500 mJ / cm. 2 The resin was then irradiated with light at 400 V and further heated at 80° C. for 30 minutes to cause curing. As a result, a laminate was obtained that had a first resin layer made of a cured resin on one side (the viewing side) of the thin glass sheet and a second resin layer made of a cured resin on the other side (the display element side).

[0097] (1) Curing resin EPICLON EXA-830LVP (a mixture of bisphenol F liquid epoxy resin and bisphenol A liquid epoxy resin, manufactured by DIC) jER YX7400N (Polyether-based liquid epoxy resin, manufactured by Mitsubishi Chemical Corporation) jER 4005P (Bisphenol F type solid epoxy resin, manufactured by Mitsubishi Chemical Corporation) jER YX8000 (hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 192~220) jER YX8034 (hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 250~360) jER YX8040 (hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 900~1500) Celloxide 2021P (3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, manufactured by Daicel Corporation) ETRENACOLL EHO (3-ethyl-3-hydroxymethyloxetane, manufactured by Ube Industries)

[0098] (2) Initiator CPI-210S (a triarylsulfonium salt type photocationic polymerization initiator, manufactured by San-Apro Co., Ltd.) DTS-200 (aromatic sulfonium salt type photocationic polymerization initiator, manufactured by Midori Kagaku Co., Ltd.) (3) Surface modifier BYK-340 (manufactured by BYK-Chemie) JAR-33 (organically modified polysiloxane, manufactured by Jujo Chemical Co., Ltd.)

[0099] <Physical property measurements> The physical properties of the cured resin products produced in Examples 13 to 25 were measured by the following methods, and the results are shown in Table 2 below.

[0100] (Storage modulus and glass transition temperature) A test piece of the cured resin with a thickness of 0.5 mm, width of 5 mm, and length of 50 mm was prepared, and a dynamic viscoelasticity spectrum was measured from -50°C to 150°C using a viscoelasticity spectrometer (IT Measurement and Control Co., Ltd., DVA-200) under the conditions of 10°C / min and 10 Hz in tension mode. From the obtained dynamic viscoelasticity spectrum, the storage modulus at 25°C was calculated. The temperature at the maximum value of the loss tangent was determined as the glass transition temperature Tg (°C).

[0101] (Young's modulus, breaking elongation, breaking strength, breaking energy) In accordance with JIS K7113 "Tensile test method for plastics", a 0.5 mm thick dumbbell-shaped (SDK-400) test piece of the cured resin was prepared and a tensile test was performed using a tensile tester. The tensile test was performed until the test piece broke, with a chuck distance of 20 mm, a tensile speed of 50 mm / min, and a sampling interval of 20 μm. From the obtained measurement results, a stress-strain curve was created with stress (unit: MPa) on the vertical axis and strain (unit: %) on the horizontal axis. The value of strain when the test piece broke was taken as the breaking elongation, and the value of maximum stress when the test piece broke was taken as the breaking strength. Young's modulus was calculated by determining the slope of the stress-strain curve at strains of 0 to 10%. The breaking energy was calculated by determining the area surrounded by the stress-strain curve and the horizontal axis.

[0102] <Evaluation> The following evaluations were carried out on the thin glass sheets of the laminates obtained in Examples 13 to 25. The results are shown in Table 2 below.

[0103] (Total light transmittance and haze) The total light transmittance and haze were measured using a HazeMeter NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.).

[0104] (Pen Drop Test) The laminate was placed with the first resin layer side facing up on a 10 mm thick artificial marble board (DuPont's "Corian"), and a ballpoint pen (BIC Japan, Orange EG0.7, nib 0.7 mmφ, weight 5.75 g) was dropped vertically from a specified height onto the first resin layer side of the laminate with the nib facing downwards. The maximum height at which no cracks occurred in the thin glass sheet was recorded as the test result.

[0105] (Shatterproof test) For the laminates in which cracks occurred in the thin glass sheets in the above-mentioned pen drop test, shatterproofness was evaluated based on the following evaluation criteria. ◯: Cracks occurred in the glass, but the glass fragmented by the cracks was held together by the resin layer, and there was no peeling between the resin layer and the thin glass sheet, so no glass shattering was observed. ×: A crack occurred in the thin glass sheet and simultaneously a crack occurred in the resin layer, causing the glass to fragment, or the resin layer and the thin glass sheet peeled off, causing the glass to fragment.

[0106] (Bending durability test) Using a U-shaped bending tester (Yuasa System Co., Ltd., DLDMLH-FS), the laminate was bent so that the first resin layer was on the inside, and repeatedly bent at a test speed of 1 second / time, a bending radius R of 2.0 mm, and 100,000 times. After the test, the bent portion of the laminate was visually inspected. The laminate was evaluated as having no change in appearance before and after the test, as "○○", as having cracks or whitening at the ends after the test but not at other parts, as "○", and as having cracks or whitening at other parts than the ends after the test and a change in appearance.

[0107] [Table 2] [Industrial Applicability]

[0108] According to the present invention, it is possible to provide a laminate having excellent impact resistance. In addition, according to the present invention, it is possible to provide an electronic device and a cover glass using the laminate, and a resin composition used for forming a resin layer of the laminate. [Explanation of symbols]

[0109] 10 Laminate 11 First resin layer 12 Thin Glass 13 Second resin layer 14 Optical transparent adhesives 15 Polarizing plate

Claims

1. A thin glass sheet having a thickness of 200 μm or less and a resin layer having a thickness of 5 μm or more arranged on at least one side of the thin glass sheet, the resin layer contains a polymer of a cationic curable resin, the cationically curable resin comprises an epoxy group-containing compound and an oxetanyl group-containing compound, the epoxy group-containing compound includes a bisphenol type epoxy resin or a hydrogenated bisphenol type epoxy resin, and an epoxy resin having a polyether skeleton, The breaking energy of the resin layer is 1 mJ / mm 3 or more, and the storage modulus at 25° C. is 2500 MPa or less. A laminate comprising:

2. 2. The laminate according to claim 1, wherein the resin layer has a Young's modulus of 50 MPa or more and 1500 MPa or less.

3. 2. The laminate according to claim 1, wherein the resin layer has a storage modulus at 25° C. of 2000 MPa or less.

4. 2. The laminate according to claim 1, wherein the resin layer has a glass transition temperature of 100° C. or lower.

5. 2. The laminate according to claim 1, wherein the hydrogenated bisphenol type epoxy resin contains a hydrogenated bisphenol A skeleton.

6. 2. The laminate according to claim 1, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2,000 or less.

7. 2. The laminate according to claim 1, wherein the epoxy resin having a polyether skeleton is liquid at 23°C.

8. 2. The laminate according to claim 1, wherein the oxetanyl group-containing compound is monofunctional.

9. 2. The laminate according to claim 1, wherein the content of the hydrogenated bisphenol type epoxy resin in the resin layer is from 20% by weight to 60% by weight, the content of the epoxy resin having a polyether skeleton is from 10% by weight to 20% by weight, and the content of the oxetanyl group-containing compound is from 20% by weight to 60% by weight.

10. A first resin layer having a thickness of 5 μm or more and disposed on one side of the thin glass; A second resin layer having a thickness of 5 μm or more is disposed on the opposite side of the thin glass to the first resin layer side, The first resin layer and the second resin layer are both formed of the resin layer. The laminate according to claim 1.

11. The laminate according to claim 10 , wherein the first resin layer and the second resin layer each have a Young's modulus of 50 MPa or more and 1500 MPa or less.

12. 11. The laminate according to claim 10, wherein at least one of the first resin layer and the second resin layer has a thickness of 25 μm or less.

13. 11. The laminate according to claim 10, wherein at least one of the first resin layer and the second resin layer has a glass transition temperature of 100° C. or lower.

14. A thin glass sheet having a thickness of 200 μm or less and a resin layer having a thickness of 5 μm or more arranged on at least one side of the thin glass sheet, the resin layer contains a polymer of a cationic curable resin, the cationically curable resin comprises an epoxy group-containing compound and an oxetanyl group-containing compound, the epoxy group-containing compound includes a bisphenol type epoxy resin or a hydrogenated bisphenol type epoxy resin, and an epoxy resin having a polyether skeleton, The Young's modulus of the resin layer is 50 MPa or more and 1500 MPa or less, The breaking energy of the resin layer is 1 mJ / mm 3 That's all. A laminate comprising:

15. The laminate according to claim 14, wherein the resin layer has a storage modulus at 25°C of 2500 MPa or less.

16. 15. The laminate according to claim 14, wherein the resin layer has a glass transition temperature of 100° C. or lower.

17. The laminate according to claim 14, wherein the hydrogenated bisphenol type epoxy resin contains a hydrogenated bisphenol A skeleton.

18. 15. The laminate according to claim 14, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2,000 or less.

19. The laminate according to claim 14, wherein the epoxy resin having a polyether skeleton is liquid at 23°C.

20. The laminate according to claim 14, wherein the oxetanyl group-containing compound is monofunctional.

21. 15. The laminate according to claim 14, wherein the content of the hydrogenated bisphenol type epoxy resin in the resin layer is from 20% by weight to 60% by weight, the content of the epoxy resin having a polyether skeleton is from 10% by weight to 20% by weight, and the content of the oxetanyl group-containing compound is from 20% by weight to 60% by weight.

22. A first resin layer having a thickness of 5 μm or more and disposed on one side of the thin glass; A second resin layer having a thickness of 5 μm or more is disposed on the opposite side of the thin glass to the first resin layer side, The first resin layer and the second resin layer are both formed of the resin layer. The laminate of claim 14.

23. 23. The laminate according to claim 22, wherein at least one of the first resin layer and the second resin layer has a storage modulus at 25°C of 3000 MPa or less.

24. 23. The laminate according to claim 22, wherein at least one of the first resin layer and the second resin layer has a thickness of 25 μm or less.

25. 23. The laminate according to claim 22, wherein at least one of the first resin layer and the second resin layer has a glass transition temperature of 100° C. or lower.

26. The laminate according to claim 22, wherein the hydrogenated bisphenol type epoxy resin contains a hydrogenated bisphenol A skeleton.

27. 23. The laminate according to claim 22, wherein the hydrogenated bisphenol type epoxy resin has an epoxy equivalent of 100 or more and 2,000 or less.

28. 23. The laminate according to claim 22, wherein the epoxy resin having a polyether skeleton is liquid at 23°C.

29. The laminate according to claim 22, wherein the oxetanyl group-containing compound is monofunctional.

30. 23. The laminate according to claim 22, wherein the content of the hydrogenated bisphenol type epoxy resin in the resin layer containing the polymer of the cationically curable resin is 20% by weight or more and 60% by weight or less, the content of the epoxy resin having a polyether skeleton is 10% by weight or more and 20% by weight or less, and the content of the oxetanyl group-containing compound is 20% by weight or more and 60% by weight or less.

31. An electronic device comprising the laminate according to any one of claims 1 to 30.

32. A cover glass comprising the laminate according to any one of claims 1 to 30.

33. A resin composition used to form a resin layer of the laminate according to any one of claims 1 to 30.

34. When applied to thin glass with a thickness of 200 μm or less, the breaking energy is 1 mJ / mm 3 or more, and is used for forming a resin layer having a storage modulus at 25°C of 2500 MPa or less, A resin composition comprising a hydrogenated bisphenol type epoxy resin, an epoxy resin having a polyether skeleton, and an oxetanyl group-containing compound.

Citation Information

Patent Citations

  • Substrate for display element and its manufacturing method

    JP2008107510A

  • Protective substrate for display unit

    JP2013037207A

  • Glass-plastic laminated devices, processing lines and methods therefor

    JP2014523352A

  • Photocurable resin composition and adhesive

    JP2018159069A

  • Photocurable resin composition and adhesive

    JP2019167415A